Biocatalytic and antibacterial visualization of green synthesized silver nanoparticles using Hemidesmus indicus. (May 2015) - Latha, M.; Sumathi, M.; Manikandan, R.; Arumugam, A.; Prabhu, N.M.
Abstract: In the present investigation, we described the green synthesis of silver nanoparticles using plant leaf extract of Hemidesmus indicus . The synthesized silver nanoparticles were characterized by UV–visible spectroscopy, fourier transform infra-red spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). TEM images proved that the synthesized silver nanoparticles were spherical in shape with an average particle size of 25.24 nm. To evaluate antibacterial efficacy, bacteria was isolated from poultry gut and subjected to 16S rRNA characterization and confirmed as Shigella sonnei . The in vitro antibacterial efficacy of synthesized silver nanoparticles was studied by agar bioassay, well diffusion and confocal laser scanning microscopy (CLSM) assay. The H. indicus mediated synthesis of silver nanoparticles shows rapid synthesis and higher inhibitory activity (34 ± 0.2 mm) against isolated bacteria S. sonnei at 40 μg/ml. Graphical abstract: Highlights: Green synthesis of silver nanoparticles is using Hemidesmus indicus . Silver nanoparticles were investigated by FTIR, XRD, EDX, TEM and UV–vis spectroscopy. Antibacterial activity is demonstrated using poultry pathogenic bacteria Shigella sonnei . S. sonnei and silver nanoparticles interaction study in CLSM.